CaAl2Cr2O7: Formation, synthesis, and characterization of a new Cr(III) compound under air atmosphere in the Al2O3–CaO–Cr2O3 system. Issue 13 (September 2019) - Nath, Mithun; Song, Shengqiang; Liu, Hang; Li, Yawei
Abstract: Despite huge potential, Al2 O3 –CaO–Cr2 O3 system has been one of the least investigated one due to the generation of carcinogenic and toxic Cr(VI) compounds. Herein, we investigated the system under air atmosphere varying Cr2 O3 while keeping Al2 O3 :CaO ratio constant in order to identify the Cr(VI) dominant region, eventually to avoid it. The Ca4 Al6 Cr VI O16 phase predominantly formed in the air atmosphere with Cr2 O3 content up to ∼12 mol%. However, an unprecedented Cr(III) phase appeared under air at higher Cr2 O3 content (26.43 mol%). We then synthesized the new polycrystalline ternary Cr(III) compound (CaAl2 Cr2 O7 ) at 1500 °C under air atmosphere for the first time. A trigonal symmetry of hexagonal crystal family with space group P3 (143), lattice parameters a = b = 7.7909 Å and c = 7.6506 Å were determined from the X-ray powder diffraction pattern study. Electron microscope studies revealed uniform hexagonal microcrystals with similar lattice parameters. Most significantly, the binding energies of 586.1 and 576.2 eV for Cr2p1/2 and Cr2p3/2 respectively implied the +3 oxidation state of Cr in this compound. Highlights: We studied the Al2 O3 –CaO–Cr2 O3 system under air to identify and avoid Cr(VI) region. An unknown Cr(III) phase under air atmosphere was observed during the study. The new phase (CaAl2 Cr2 O7 ) was synthesized at 1500 °C under air for the first time. Trigonal symmetry (space group P3, 143; lattice parameters a  =  b  = 7.7887 Å, c  = 7.6506 Å, α = β = 90, γ = 120) was determined by XRD. XPS studies confirm the +3 oxidation state of Cr in this phase.